MEASUREMENTS, ANALYSIS AND EFFECT OF ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) TOWARDS EMPLOYEE PERFORMANCE - Tiena Gustina Amran; Gusti Agung Sanjaya Setyanegara (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Organizational culture is values that are held firmly by an organization / company and become guidelines for members of the organization in carrying out their activities. Guidelines called organizational culture are written or unwritten. Every activity carried out should be based on existing organizational cultural values. However, in applying the organizational culture does it have a significant influence on members of the organization. This study aims to identify the type of organizational culture using the Organizational Culture Assessment Instrument (OCAI), analyze the influence of organizational culture on employee performance, and use OCAI results for management of change activities. Steps taken to develop organizational culture by identifying the type of organizational culture applied in company so far and compare it with the type of organizational culture desired in the future. Data collection techniques used 2 kinds of questionnaires and interviews. The first questionnaire will be used to determine the nature of the company's organizational culture with the OCAI method, and then be given development according to the nature of the organizational culture expected by future members of the organization. As a result, the type of organizational culture is in fact a "market" that is more focused on product results, while what employees want is a "clan" that prioritizes the improvement of the skills of the employees themselves. Multi-linear regression method is used to see the effect on employee performance. Organizational culture has enough influence on employee performance with a percentage of 88.9 percent. Meanwhile, the organizational culture that most influences employee performance is "hierarchy". Two change alternatives are formed, namely based on "hierarchy" and "clan" organizational culture. Keywords: OCAI, Multi-linear regression, Organization culture